Semantic displacement of place, (when memory becomes home) poetry collection: Analytical study - Al Btoosh, Hosam Mohammad (Journal of Humanities & Social Sciences, 2021)
The study addressed with research and analysis, semantic shifts in place patterns in the anecdotal group entitled (When the memory becomes home) for Hend Abu-Shaar, where the researcher collected the places mentioned in this anecdotal group, and found that they range from public, closed, safe, and frightening places, attractive, repulsive, centralized, and marginal, and by identifying these places and their knowledge, the search has risen in search of the intended shifts that the writer wanted in her stories, to express narrative circles in which events interact with each other to push the narration wheel forward, by describing the place and the events and circumstance of the characters. The study concluded to a number of results, the most important of which are: different places appeared in this anecdotal group, with emotional and psychological characteristics, characterized by power sometimes and compassionate at other times, and by softness at times and by violence at other times, and the interacting characters in the narrative circles based on these places were directly affected The place where it occurs, because the place is the pot of events, and it is with the characters rooted in it.